(untitled) (Global Journal of Human-Social Science, 2021)
The present paper evidences the relation between memory, history and rhetorical education in some of Machado’s narratives. In this research, the analyzed narrator and characters are medallions that alienate themselves with the cultural models left by the west, for instance, those of political ethics present in the writings of Machiavelli and those of the uses and customs of the rhetorical institution. In fact, in these narratives, the reference made by their characters to the memory and the history as places of discourse invention contradict the moral conventions of the ancient oratory, such as those of speaking well and honestly, which makes verisimilar the idea in which these narratives are metaphors of an empire whose educational system is dominated by subjects who, when ordering the discourse according to the needs of the occasion, take power as the ultimate cause of their reasoning.